Zinc Detection in Serum by Anodic Stripping Voltammetry on Microfabricated Bismuth Electrodes. Issue 2 (22nd January 2013) - Jothimuthu, Preetha; Wilson, Robert A.; Herren, Josi; Pei, Xing; Kang, Wenjing; Daniels, Rodney; Wong, Hector; Beyette, Fred; Heineman, William R.; Papautsky, Ian
Abstract Zinc (Zn) homeostasis is required for a functional immune system. Critically ill patients often exhibit decreased Zn serum concentrations and could potentially benefit from Zn supplementation as a therapeutic strategy. However, the conventional approaches to monitoring Zn are time consuming and costly. This work reports on detection of Zn by anodic stripping voltammetry (ASV) on bismuth electrodes in a microfabricated electrochemical cell. The working potential window of the electrodeposited bismuth film electrode was investigated by cyclic voltammetry, while square wave ASV was used for measuring Zn in acetate buffer and blood serum. Conditions critical to sensing, such as preconcentration potential, preconcentration time, and buffer pH, were optimized for Zn detection. The sensor was successfully calibrated with pH 6 acetate buffer in the physiologically‐relevant range of 5 µM to 50 µM Zn and exhibited well‐defined and highly repeatable peaks. The sensor was used to demonstrate measurement of Zn in blood serum digested in HCl. The results of this work show that Zn detection in serum is possible with smaller sample volumes (µL vs. mL) and faster turnaround time (hours vs. days) as compared with the conventional spectroscopic methods.